Basal Plane Hydrogen Evolution Activity from Mixed Metal Nitride MXenes Measured by Scanning Electrochemical Microscopy. (19th May 2020) - Djire, Abdoulaye; Wang, Xiang; Xiao, Chuanxiao; Nwamba, O. Charles; Mirkin, Michael V.; Neale, Nathan R.
Abstract: 2D early transition metal carbide and nitride MXenes have intriguing properties for electrochemical energy storage and electrocatalysis. These properties can be manipulated by modifying the basal plane chemistry. Here, mixed transition metal nitride MXenes, M‐Ti4 N3 Tx (M = V, Cr, Mo, or Mn; Tx = O and/or OH), are developed by modifying pristine exfoliated Ti4 N3 Tx MXene with V, Cr, Mo, and Mn salts using a simple solution‐based method. The resulting mixed transition metal nitride MXenes contain 6–51% metal loading (cf. Ti) that exhibit rich electrochemistry including highly tunable hydrogen evolution reaction (HER) electrocatalytic activity in a 0.5 m H2 SO4 electrolyte as follows: V‐Ti4 N3 Tx > Cr‐Ti4 N3 Tx > Mo‐Ti4 N3 Tx > Mn‐Ti4 N3 Tx > pristine Ti4 N3 Tx with overpotentials as low as 330 mV at −10 mA cm −2 with a charge‐transfer resistance of 70 Ω. Scanning electrochemical microscopy (SECM) reveals the electrochemical activity of individual MXene flakes. The SECM data corroborate the bulk HER activity trend for M‐Ti4 N3 Tx as well as provide the first experimental evidence that HER results from catalysis on the MXene basal plane. These electrocatalytic results demonstrate a new pathway to tune the electrochemical properties of MXenes for water splitting and related electrochemical applications. Abstract : Mixed transition metal nitride MXenes M‐Ti4 N3 Tx (M = V, Cr, Mo, or Mn) are prepared using a simple solution‐based method. These M‐Ti4 N3 Tx exhibit highly tunable electrochemical behavior based on the transition metal M including hydrogen evolution activity from the basal planes as measured via scanning electrochemical microscopy.